2015
DOI: 10.1186/s12890-015-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between obstructive sleep apnea and metabolic syndrome: a systematic review and meta-analysis

Abstract: BackgroundObstructive sleep apnea (OSA) is characterized by repeated episodes of obstruction of the upper airway. Numerous studies have indicated a relationship between OSA and metabolic syndrome (MS), but the results remain debatable. We aimed to perform a systematic review and meta-analysis to evaluate the association between OSA and MS.MethodsWe searched electronic databases (PubMed, EMBASE, and ISO Web of Knowledge) up to September 2014 with English-language restriction. Cross-sectional, case–control, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 58 publications
1
77
0
3
Order By: Relevance
“…5 Both OSA and HT are comorbidities of obesity and are related to metabolic syndrome. 6,7 In some patients, HT may be solely secondary to OSA. It is presumed that the arterial blood pressure (BP) is elevated by intermittent hypoxemia during the night, which activates the sympathetic system via peripheral and central chemoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…5 Both OSA and HT are comorbidities of obesity and are related to metabolic syndrome. 6,7 In some patients, HT may be solely secondary to OSA. It is presumed that the arterial blood pressure (BP) is elevated by intermittent hypoxemia during the night, which activates the sympathetic system via peripheral and central chemoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis, OSAHS was showed to be associated with MS, although causality between these alterations has not been demonstrated [21]. Why patients with syndrome Z can present more alterations than patients with OSHAS only?…”
Section: Comparison With Other Studies and Explanationsmentioning
confidence: 99%
“…Studies have shown that OSA is associated with an increased risk of hypertension, congestive heart failure, type II diabetes, stroke, and premature death. [1][2][3][4] This is an area of growing public health concern as the most current data show that the prevalence of moderate to severe OSA ranges from 10% to 17% in men and from 3% to 9% in women, a notable increase of >25% over the last 2 decades. 5 Obesity is a known causal factor for OSA, and studies estimate that over 50% of the moderate to severe OSA cases occur in patients with an elevated body mass index (BMI).…”
mentioning
confidence: 99%
“…2,3 The outcome of patients with small subsegmental pulmonary emboli in whom anticoagulation is withheld has not been established clearly by randomized trials or retrospective analyses. 4 Many technical factors can influence the quality of the CTA, including respiratory motion, the timing of contrast injection, and image artifact. The interpretation of these suboptimal studies may result in false-positive or false-negative results, with significant variability in the interobserver agreement among different radiologists.…”
mentioning
confidence: 99%